Consensus Statement on Public Involvement and Engagement with Data-Intensive Health Research - Aitken, Mhairi; Tully, Mary P; Porteous, Carol; Denegri, Simon; Cunningham-Burley, Sarah; Banner, Natalie; Black, Corri; Burgess, Michael; Cross, Lynsey; Van Delden, Johannes; Ford, Elizabeth; Fox, Sarah; et al. (International journal of population data science, 2019)
This consensus statement reflects the deliberations of an international group of stakeholders with a range of expertise in public involvement and engagement (PI&E) relating to data-intensive health research. It sets out eight key principles to establish a secure role for PI&E in and with the research community internationally and ensure best practice in its execution. Our aim is to promote culture change and societal benefits through ensuring a socially responsible trajectory for innovations in this field. Our key premise is that the public should not be characterised as a problem to be overcome but a key part of the solution to establish socially beneficial data-intensive health research for all.